Unilateral biportal endoscopic lumbar interbody fusion versus minimally invasive transforaminal lumbar interbody fusion for single-segment lumbar degenerative disease: a meta-analysis - Yanxing He; Qianyue Cheng; Jiang She (BMC Musculoskeletal Disorders)
Abstract Background Minimally invasive spine surgery has seen rapid development in recent years. The purpose of this study was to evaluate the use of unilateral biportal endoscopic lumbar interbody fusion (ULIF) versus minimally invasive surgery transforaminal interbody fusion (MIS-TLIF) for the treatment of single-segment lumbar degenerative disease (LDD) through a systematic review and meta-analysis. Methods In collaboration with various search terms, a comprehensive examination of the scientific literature was carried out using PubMed, China National Knowledge Infrastructure (CNKI), Wanfang, and other databases. A total of 9 studies were included retrospective cohort studies. Results We observed statistically significant differences in intraoperative blood loss, total hospital stay, postoperative hospital stays, and 1-month postoperative Oswestry Disability Index (ODI) scores between the ULIF and MIS-TLIF groups, with the ULIF group being more dominant. MIS-TLIF group was statistically more advantageous in terms of operative time. There were no statistically significant differences in postoperative visual analogue scale (VAS) scores, 3-month postoperative and final ODI scores, excellent and good rate, complications, disc heights, and lumbar lordosis angle between the two groups. Conclusions Treatment of single-segment LDD with ULIF and MIS-TLIF is both safe and effective. ULIF has the advantage of less intraoperative blood loss, shorter total hospital stay, shorter postoperative hospital stay, and lower ODI scores at 1 month postoperatively compared to MIS-TLIF. There were no significant differences between ULIF and MIS-TLIF in the treatment of LDD in terms of postoperative VAS scores, 3-month postoperative and final ODI scores, satisfaction rates, fusion rates, complications, disc heights, and lumbar lordosis angle. MIS-TLIF has a shorter procedure time than ULIF.